Seskviterpenové laktony: od plevelu k léčivu - Peterková, Lucie; Rimpelová, Silvie; Kmoníčková, Eva; Ruml, Tomáš (Chemické listy, 2019)
Sesquiterpene lactones are bioactive natural compounds with anticancer, antiprotozoal, immunomodulatory, antibacterial and antiviral activity which have potential for drug development. The aim of this review article is to provide a brief insight into the field of sesquiterpene lactones: the main mechanisms of their biological actions, as well as particular compounds, are described, some of which have already become a basis of a drug development and are being tested in clinical trials.
Keywords: Sesquiterpenes, Guaiane; Pharmacognosy; artemisininy; Tanacetum parthenium; fytogenní protinádorové látky; Enzyme Inhibitors; Artemisinins; Immunomodulation; Sesquiterpenes; thapsigargin; seskviterpeny; laktony; Antineoplastic Agents, Phytogenic; Ethnopharmacology; seskviterpeny guajanové; inhibitory enzymů; etnofarmakologie; imunomodulace; Lactones; Thapsigargin; farmakognozie